Evaluation of The Antidepressant Properties of Aqueous Extract Terminalia Chebula Fruit Pulp in Wistar Albino Rats.: Pharmaceutical Science-Pharmacology - Choudhary, Arbind Kumar; Manivannan, E; Ramalingam, Kothai; Sivasankari, V.; Balasubramanian, Arul; Rajan, Chandrashekar (International Journal of Life Science and Pharma Research, 2022)
Between 9 and 46% of those being treated for major depressive disorder had a partial or no response to antidepressants. Research is needed to produce a more effective and safer antidepressant. Terminalia chebula stimulates the CNS. The major goal of this research is to determine whether chronic administration of aqueous extract of Terminalia chebula fruit pulp dosages of (100, 200, and 400 mg/kg) have antidepressant effects. Terminalia chebula behavioural model of rats when supplied over three to four months in experimental rats. Wistar albino rats weighing 200 to 300 grams and one to two months old were utilized. For all experiments, healthy wistar albino rats of either sex were separated into six groups with equal numbers of animals. The antidepressant properties of Terminalia chebula fruit pulp were investigated using two different experimental methods. Both the forced swimming and the tail suspension tests fall into this category. Terminalia chebula fruit pulp was given at doses of 100 mg/kg, 200 mg/kg, and 400 mg/kg. To treat depression, a standard dose of antidepressant medication (10 mg/kg) of imipramine was administered. Each group of rats was tested one hour after treatment. A rat behavioural stress paradigm found that Terminalia chebula had a nephroprotective effect. Antioxidant phytochemicals like Terminalia chebula were extracted and quantified. The abundance of phytochemicals implies that this might be a good source for antioxidants and depression therapy. The current evidence is intriguing and may be employed as a medicine candidate after additional study and clinical tests.